On the cotypeset of torsion-free abelian groups - Karimi, F. (Algebra and Discrete Mathematics, 2015)
In this paper the cotypeset of some torsion-free abelian groups of
finite rank is studied. In particular, we determine the cotypeset
of some rank two groups using the elements of their typesets.